Methods of sampling and test for carbonaceous materials used in aluminium manufacture. Cold ramming pastes. Preparation of baked rammed test pieces and determination of baked apparent density, change in volume and loss in mass Part 4.7, (30th September 1991) - British Standards Institution,
No abstract available